Comprehensive analysis of nonsurrounded nucleolus and surrounded nucleolus oocytes on chromatin accessibility using ATAC‐seq. Issue 2 (4th January 2023) - Sun, Xiaofan; Wang, Dayu; Li, Weijian; Gao, Qian; Tao, Jingli; Liu, Honglin
Abstract: Mouse germinal vesicle (GV) oocytes are divided into surrounded nucleolus (SN) and nonsurrounded nucleolus (NSN) oocytes based on chromatin morphology. NSN oocytes spontaneously transform into SN oocytes after accumulating enough maternal transcripts. SN oocytes show transcriptional silencing. When oocyte maturation is abnormal or takes place in vitro, NSN oocytes do not go through SN stage before proceeding to MII. Nontransitive oocytes show developmental retardation, a low fertilization rate, and arrest at the two‐cell embryo stage in mice. Here, chromatin‐binding ribonucleic acid polymerase II (RNAP II) activity, newly synthesized RNA, and chromatin accessibility in GV oocytes were examined. In SN oocytes, RNAP II did not bind to DNA, neo‐RNA was not generated in nuclei, and the phosphorylation state of RNAP II did not affect the chromatin‐binding activity. The number of accessible genes in SN oocytes was remarkably lower than that in NSN oocytes. The accessibility of different functional genes was also different between the two types of oocytes. Thus, low chromatin accessibility leads to transcriptional silencing in SN oocytes.